If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2y + z = -1x + 2 Reorder the terms: 3x + -2y + z = 2 + -1x Solving 3x + -2y + z = 2 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 3x + -2y + x + z = 2 + -1x + x Reorder the terms: 3x + x + -2y + z = 2 + -1x + x Combine like terms: 3x + x = 4x 4x + -2y + z = 2 + -1x + x Combine like terms: -1x + x = 0 4x + -2y + z = 2 + 0 4x + -2y + z = 2 Add '2y' to each side of the equation. 4x + -2y + 2y + z = 2 + 2y Combine like terms: -2y + 2y = 0 4x + 0 + z = 2 + 2y 4x + z = 2 + 2y Add '-1z' to each side of the equation. 4x + z + -1z = 2 + 2y + -1z Combine like terms: z + -1z = 0 4x + 0 = 2 + 2y + -1z 4x = 2 + 2y + -1z Divide each side by '4'. x = 0.5 + 0.5y + -0.25z Simplifying x = 0.5 + 0.5y + -0.25z
| -2+-2+-.57+-.57+-.57+-.57= | | -237=b/21+(-225) | | m/2+m/6=8 | | 4r+3=10r+6 | | 5(x-5)=3(x-7) | | 9x-9=6x+19 | | -3t-7+7t=34+9t-2 | | a/4=12x4 | | In(x+4)+In(x)=In(x+40) | | 1/10x-3/5y=2/5 | | 3xy-9x^2y+12x^3=0 | | 6r+24=6 | | -(3xy-9)+4(3xy+8)= | | 30(3b-7)=90 | | 3x+x+3/7=4 | | -1a^2-12a-70=0 | | 21.453=4.8-5n+2.9n | | 12m-15=6(2m+5) | | -8x+3y-48=0 | | 17z-12=668 | | 8(3a-6)=9(2a-4) | | (.18y-4)+.06y=.10y-1 | | 5x-3=5+3x | | 2x-9+10=x+6 | | 213+3j=531 | | 4x+8=7x-19 | | 6.408*100000.00= | | 5(n+1)=2(n+7) | | 1.8(r)+9=-5.7(r)-6 | | 2-(5x+10)-2(x-7)=2x+6 | | n/-6+(-29)=-33 | | 4(a+8)=4(a-6) |